Financial Statement Analysis as a Basis for Strategic Decision Making in MSMEs: A Case Study of Liquidity, Profitability, and Cash Flow Management - Jusuf Nurdin; Nuniek Dewi Pramanik (CV Edujavare Publishing, 2025)
Financial reports play a crucial role in supporting strategic decision-making for micro, small, and medium enterprises (MSMEs). However, in practice, many MSMEs have not maximized the use of financial reports as a foundation for business evaluation and management decision-making. This article aims to examine the function of financial reports in business decision-making through a descriptive-analytical method, using a case study of an MSME in the culinary sector. The analysis focuses on the elements of financial reports, liquidity ratios, solvency, profitability, and cash flow, along with their implications for business strategy. Key findings reveal that high profits do not always reflect a healthy business if they are not accompanied by consistent operational cash flow. The case study of the MSME